The phenomenon of mobbing in the opinion of the professionally active - Firlej, Ewelina; Janiszewska, Mariola; Byzdra, Mariusz; Pawlikowska-Łagód, Katarzyna; Dąbska, Olga (Journal of Education, Health and Sport, 2017)
Introduction The phenomenon of mobbing affects many employees irrespective of their profession. One of the main manifestations of persecution in the workplace is the constant criticism, ridicule, undermining of professional skills and the use of threats. Employees in spite of harassment do not reveal their problem because of fear of losing their jobs. Mobbing, whatever the form it takes, negatively affects the self-esteem and mental health of each employee. Aim The aim of the study was to investigate the incidence of mobbing among the working population. Material and methods 72 people participated in the study. Men accounted for 50.71%, women 49.29%. Using the diagnostic survey method, survey technique. The research tool was the author's questionnaire survey. The questions in the questionnaire concerned the socio-demographic situation of the respondents and the conditions and general atmosphere at work. The research was conducted from April to July 2016. Results Mobbing at work affected a large proportion of the respondents. Its main manifestations were continuous criticism of work done, questioning decisions, ridicule and threatening and oral threats. The perpetrator of the persecution was mostly a male co-worker. Only a few victims of mobbing reported a problem to the police and confessed to their friends. Conclusions Mobbing is a dangerous phenomenon that negatively affects the worker's efficiency and involvement in the job. It is very important to make employers aware of the consequences of mobbing and educate workers on the actions they should take to become victims.